The impact of endogenous content, replicates and pooling on genome capture from faecal samples. (4th December 2017) - Hernandez‐Rodriguez, Jessica; Arandjelovic, Mimi; Lester, Jack; de Filippo, Cesare; Weihmann, Antje; Meyer, Matthias; Angedakin, Samuel; Casals, Ferran; Navarro, Arcadi; Vigilant, Linda; Kühl, Hjalmar S.; Langergraber, Kevin; et al.
Abstract: Target‐capture approach has improved over the past years, proving to be very efficient tool for selectively sequencing genetic regions of interest. These methods have also allowed the use of noninvasive samples such as faeces (characterized by their low quantity and quality of endogenous DNA) to be used in conservation genomic, evolution and population genetic studies. Here we aim to test different protocols and strategies for exome capture using the Roche SeqCap EZ Developer kit (57.5 Mb). First, we captured a complex pool of DNA libraries. Second, we assessed the influence of using more than one faecal sample, extract and/or library from the same individual, to evaluate its effect on the molecular complexity of the experiment. We validated our experiments with 18 chimpanzee faecal samples collected from two field sites as a part of the Pan African Programme: The Cultured Chimpanzee. Those two field sites are in Kibale National Park, Uganda ( N = 9) and Loango National Park, Gabon ( N = 9). We demonstrate that at least 16 libraries can be pooled, target enriched through hybridization, and sequenced allowing for the genotyping of 951, 949 exome markers for population genetic analyses. Further, we observe that molecule richness, and thus, data acquisition, increase when using multiple libraries from the same extract or multiple extracts from the same sample. Finally, repeated captures significantly decrease the proportion of off‐target reads from 34.15% after one capture round to 7.83% after two capture rounds, supporting our conclusion that two rounds of target enrichment are advisable when using complex faecal samples.